Affective semiosis and affective logic. (January 2018) - Tateo, Luca
Abstract: Psychology values consistency, reduction of uncertainty, causality and continuity as normative aspects of mental life. Even though theories of dynamic equilibrium include phenomena of ruptures, homeostasis and tension as part of the psychological functioning, these are understood as momentary alterations of a condition that must be restored in order to maintain the integrity of the system. Yet in everyday life one can observe phenomena in which human beings constantly move ahead the conditions of living and the limits of what is somehow acceptable. Tension, ambivalence and uncertainty are part of existence and the most part of us can perfectly live with it, if not actively looking for it. Traditional logic underneath psychology cannot account for this meaning-making process. We then need to think about a specific form of affective logic that can enable us to understand extreme phenomena not as pathologies but as special forms of meaning-making. I will outline an affective semiosis process based on an affective logic, drawing from the ideas of Peirce's semiotics, Meinong's theory of objectives, Wittegenstein's concept of "seeing-as", Herbst's co-genetic logic and Simmel's complementarity between binding and unbinding.